LEGAL ANALYSIS OF WIFE'S INHERITANCE RIGHTS TO HUSBAND'S PROPERTY IN ISLAMIC INHERITANCE LAW (STUDY OF DECISION NUMBER 2563/PDT.G/2023/PA.Mdn) - Muhammad Yaasir Syauqii Pohan; Hasim Purba; Utary Maharany Barus (PT. Radja Intercontinental Publishing, 2024)
This study aims to analyze the legal position of the wife regarding the husband's inherited property from the perspective of Islamic inheritance law, with a case study on Decision Number 2563/Pdt.G/2023/PA.Mdn. The focus of this study is to examine how Islamic inheritance law regulates the wife's rights to the husband's inherited property after the husband dies, and how religious courts apply these legal provisions in resolving inheritance disputes. The research method used is normative juridical with a case approach. The data analyzed include primary legal materials in the form of the Qur'an, Hadith, and related laws and regulations, as well as secondary legal materials in the form of Islamic legal literature and expert doctrines. In addition, this study also examines court decision documents to understand the legal considerations used by the panel of judges. The results of the study show that in Islamic inheritance law, the wife has the right to a certain portion of the husband's inheritance, which is specifically regulated in the Qur'an, Surah An-Nisa verse 12. However, the husband's inherited property that is not included in the category of joint property remains part of the inheritance that must be divided according to the provisions of faraidh law. In Decision Number 2563/Pdt.G/2023/PA.Mdn, the panel of judges decided that the wife is entitled to a portion according to the provisions of faraidh, while still considering the status of the property as inherited property that is not mixed with joint property. This study provides an important contribution in strengthening the understanding of the application of Islamic inheritance law in Indonesia, especially regarding the rights of wives to their husbands' inherited property. In addition, the results of this study can be a reference for legal practitioners, academics, and the community in understanding and resolving inheritance disputes fairly and in accordance with sharia.